ANALISIS FAKTOR YANG BERPENGARUH TERHADAP PILIHAN KUNJUNGAN PARIWISATA PASAR TERAPUNG DI KOTA BANJARMASIN - DWI KLAUDIA PEBRIANA SANTI (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2018)
This study aims to (1) find out the dominant factor determining tourist visit to the tourism object of Siring Tendean Floating Market and Muara Kuin Floating Market in Banjarmasin City; and (2) to know knowing the preferences of tourists on the choice of visits to the Siring Tendean Floating Market and Muara Kuin Floating MarketResearch respondents are 5 respondents who are considered to have an effect on the development and development of Tourism in Banjarmasin City that can be used in data processing. Data is processed by using AHP (Analytical Hierarchy Process).The results of this study indicate that mileage, accommodation, and characteristics are factors or criteria that can affect the interest of tourists and the people of Banjarmasin City to visit the attractions of the Floating Market Siring Tendean and Muara Kuin Floating Market with a reference sequence of 62% for Feature Typical, 24% for Distance, and last 14% for Accommodation. From these factors to the preferences of the choice of tourists to the choice of visits to the Floating Market Siring Tendean Ascension 74% and Muara Kuin Floating Market of 26%. With the conclusion Siring Tendean Floating Market is more dominant that is equal to 74% Keywords: Tourism, Tourist Attraction, Floating Market, Siring Tendean, Muara Kuin, AHP Method